Cobalt–free La0.5Sr0.5Fe0.9Mo0.1O3–δ electrode for symmetrical SOFC running on H2 and CO fuels. (10th October 2019) - Cai, Hongdong; Zhang, Leilei; Xu, Jingsheng; Huang, Jinhua; Wei, XiaoLi; Wang, Li; Song, Zhaoyuan; Long, Wen
Abstract: Cobalt–free perovskite La0.5 Sr0.5 Fe0.9 Mo0.1 O3– δ (LSFMo) was evaluated as the electrode of symmetrical SOFC (S–SOFC) using H2 and CO as fuels. XRD results demonstrate that the LSFMo electrode is redox stable at a temperature below 800 °C. Furthermore, the chemical compatibility of LSFMo electrode with both Sm0.2 Ce0.8 O1.95 (SDC) and La0.9 Sr0.1 Ga0.8 Mg0.2 O3–δ (LSGM) electrolytes was assessed. The thermal expansion coefficients (TECs) of the LSFMo at 30–850 °C are 13.4 × 10 −6 K −1 in air and 15.1 × 10 −6 K −1 in 5% H2 /Ar. However, for the pre–reduced LSFMo, the TEC in 5% H2 /Ar decreases to 11.8 × 10 −6 K −1 . Using LSFMo as symmetrical electrode of S–SOFCs, the maximum power densities ( P max ) of 562 mW cm −2 in dry H2 and 474 mW cm −2 in dry CO at 750 °C are attained based on 300 μm thick SDC electrolyte, while based on the LSGM electrolyte with same thickness, the P max attain 508 mW cm −2 in dry H2 and 379 mW cm −2 in dry CO. For the LSGM supported S–SOFC, the total polarization resistances ( R p ) attain 0.460 Ω cm 2 in dry H2 and 1.099 Ω cm 2 in dry CO at 750 °C. Additionally, the S–SOFCs with LSFMo electrode exhibit good power cycling stability, long–term stability and multiple redox and thermal cycling stability. Above results indicate that the LSFMo material is a very potential symmetrical electrode for S–SOFCs. Highlights: LSFMo was evaluated as electrode of S–SOFCs with SDC/LSGM electrolytes. LSFMo electrode is redox stable at IT-SOFC operating temperatures. LSFMo electrode exhibits good thermal expansion match with SDC/LSGM electrolytes. Good electrochemical performances for S–SOFCs with LSFMo electrode were obtained. Excellent cell stability for S–SOFCs with LSFMo electrode was obtained.